2019
DOI: 10.1016/j.bmc.2019.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of distal and proximal fleximer base analogues and evaluation in the nucleocapsid protein of HIV-1

Abstract: A B S T R A C TAnti-HIV-1 drug design has been notably challenging due to the virus' ability to mutate and develop immunity against commercially available drugs. The aims of this project were to develop a series of fleximer base analogues that not only possess inherent flexibility that can remain active when faced with binding site mutations, but also target a non-canonical, highly conserved target: the nucleocapsid protein of HIV (NC). The compounds were predicted by computational studies not to function via … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…In state-of-the-art progress, three classes of NC inhibitors have been explored: (i) covalent modifiers that bind to NC zinc-coordinating residues or directly to the Zn(II) ions that are crucial for NC activity; (ii) small molecules that bind to nucleic acids targets of the NC; (iii) non-covalent NC binders that compete with nucleic acids for the binding site on the NC surface [ 7 ]. While NC inhibitors of classes (i) and (ii) are most suited as topical microbicides because of their weak selectivity and specificity for the NC that might lead to cytotoxic effects, class (iii) inhibitors have a higher potentiality for being developed as novel anti-HIV-1 systemic drugs [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. It is worth noting that natural products have played an important role in the discovery of NC inhibitors [ 16 , 21 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…In state-of-the-art progress, three classes of NC inhibitors have been explored: (i) covalent modifiers that bind to NC zinc-coordinating residues or directly to the Zn(II) ions that are crucial for NC activity; (ii) small molecules that bind to nucleic acids targets of the NC; (iii) non-covalent NC binders that compete with nucleic acids for the binding site on the NC surface [ 7 ]. While NC inhibitors of classes (i) and (ii) are most suited as topical microbicides because of their weak selectivity and specificity for the NC that might lead to cytotoxic effects, class (iii) inhibitors have a higher potentiality for being developed as novel anti-HIV-1 systemic drugs [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. It is worth noting that natural products have played an important role in the discovery of NC inhibitors [ 16 , 21 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Final attempts at employing the di-boc protecting group tried protecting the stannyl pyrimidine 18 ; however, this method also proved ineffective. As such, attention turned toward using an in situ protection of the amine group followed by Negishi conditions for the 5- i PrAc and 5- t BuAc compounds, as these conditions had previously been successful for other fleximers developed in our lab (Scheme 7) [22].…”
Section: Resultsmentioning
confidence: 99%
“…Structural modification of natural products is one of the most effective methods to develop novel green pesticides. It is reported that 1,2,3,4-tetrahydroquinoline (THQ), which is widely distributed in natural products (Figure ), shows good activities such as antitumor activities, antimalarial activities, antivirus activities, and so on. More interestingly, some compounds possess excellent fungal CHS inhibitory activities together with remarkable antifungal activities. Additionally, pyrimidine is an active scaffold existing in a variety of commercial fungicides, such as azoxystrobin and pyrimethanil (Figure ). Pyrimidine amine or pyrimidine ether derivatives also have been extensively studied owing to their remarkable activities, such as antifungal activities, antitumor activities, antivirus activities, and so on. …”
Section: Introductionmentioning
confidence: 99%